A study of performance and reliability of port container terminal operation: case of Pelabuhan Tanjung Pelepas Sdn Bhd / Othman Ibrahim, Suhaini Mohammad and Ghazali Jamil - Ibrahim, Othman; Mohammad, Suhaini; Jamil, Ghazali (2004)
Seaports have played a very integral and prominent role in the socio-economic development of a country. Sea transport is the most preferable mode to move large volume of cargoes from one country to another. Seaport is a major facility in sea transport industry for the loading, unloading and movement of cargo to and from ship or vessel. Port of Tanjung Pelepas has become a solution for the problem and this newest port in Malaysia is specialized in handling containers for import-export and also transshipment. PTP being the new player in the highly competitive industry has to strive for excellence from Day 1 in providing its services with the zero defect mentality driven into the work culture across the board. This research will provide the insight on the importance of leveraging the company service performance and reliability in terms of port information, navigational aids, pilotage and overall loading and unloading operation. Through this research PTP is able to measure the level of customer satisfaction towards its products and services. The research result will ultimately be assisting the company in evaluating the efficiencies and productivity of the company's operation in particular on the container terminal operation besides improving current business process to be more innovative and creative in meeting both stakeholders and shareholders. On top of that, it could also assist in formulating or improving the current strategies and marketing program.